Chronic heart failure-induced skeletal muscle atrophy, necrosis, and changes in myogenic regulatory factors. - Martinez, Paula F; Okoshi, Katashi; Zornoff, Leonardo A M; Carvalho, Robson F; Oliveira Junior, Silvio A; Lima, Aline R R; Campos, Dijon H S; Damatto, Ricardo L; Padovani, Carlos R; Nogueira, Celia R; Dal Pai-Silva, Maeli; Okoshi, Marina P (My University, 2010)
Although intrinsic skeletal muscle abnormalities can influence exercise intolerance during heart failure (HF), the factors responsible for muscle changes have not been elucidated. In this study we evaluated the expression of myogenic regulatory factors (MRF), myosin heavy chain (MyHC) isoforms, and fiber trophism in the soleus muscle of rats with myocardial infarction-induced heart failure. Six months after surgery, 2 groups of rats were studied: sham, and infarcted rats with HF (MI/HF+, MI size: 41.1±6.3% of total left ventricular area). In the infarcted group, microscopic evaluation revealed scattered foci of fiber necrosis in combination with inflammatory cells, phagocytosis, and increased fibrous tissue. The frequency of necrotic fibers was significantly higher in the MI/HF+ group than in the sham. The MI/HF+ group had atrophy of type I, IC/IIC, and IIA fibers compared to the sham group (P<0.05). MyoD gene expression was higher in the MI/HF+ group (sham: 1.00±0.49; MI/HF+: 2.53±0.71 arbitrary units; P<0.001). Myogenin and MRF4 gene expression was similar in both groups. Myogenin protein levels were reduced in the MI/HF+ group (sham: 1.00±0.21; MI/HF+: 0.74±0.21 arbitrary units; P=0.026). MyoD and MRF4 protein levels, as well as the MyHC distribution, were not different between groups. The MI/HF+ group had higher TNF-α and IL-6 serum concentrations than the sham group. Heart failure-induced skeletal muscle atrophy is combined with fiber necrosis, increased MyoD gene expression and decreased myogenin protein levels.